On the Comparison Between the Nc/CRN and the Ne/ERN - Vidal, Franck; Burle, Boris; Hasbroucq, Thierry (Frontiers in Human Neuroscience, 2022)
After the Error Negativity (Ne or ERN) has been described on full-blown errors and on partial error, a smaller Error Negativity-like wave (CRN or Nc) has also been evidenced on correct trials, first in schizophrenic patients and, later on, in healthy subjects. The functional significance of the Nc, as compared to the, Ne is of critical importance, since most models accounting for the genesis of the Ne on errors and partial errors cannot account for the existence of the Nc if this Nc simply corresponds to a small Ne. On the contrary, if the Nc and the Ne are two completely distinct components, then the existence of a Nc poses no constraint to the existing models. To this end, we examine in the present review the similarities and the differences existing between the Ne and the Nc regarding their functional properties and their anatomical origin.